Oxide modified positive electrode material as well as preparation method and application thereof

By using the interaction between metal salts, precursor alcohol solvents and anti-solvents on the surface of the battery electrode material, uniform, continuous and thickness-controllable oxide coating is achieved, and the problem of uneven coating in the prior art is solved, which significantly improves the cycle stability and rate performance of the battery.

CN119735243APending Publication Date: 2025-04-01INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311263384.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform, continuous and controllable oxide coating on the surface of the electrode material of the battery, resulting in the impact of the cycle stability and safety of the battery.

Method used

By reacting the metal salt with the precursor alcohol solvent to form solution A, the coating substrate material is mixed with the anti-solvent to form solution B, and the two are mixed under stirring, the feeding method and speed are controlled to achieve a uniform, continuous and controllable surface thickness of the cladding layer.

Benefits of technology

It realizes uniform coating of the surface of the electrode material, significantly improves the cycle stability and rate performance of the battery, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735243A_ABST
    Figure CN119735243A_ABST
Patent Text Reader

Abstract

The invention provides an oxide-modified positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: 1) reacting metal salt with a precursor alcohol solvent for a certain time to form a solution A; 2) mixing the coated substrate material with an anti-solvent to form a solution B; (3) mixing the solution A obtained in the step (1) with the solution B obtained in the step (2), and forming a uniform and continuous coating layer with controllable thickness on the surface of the coating substrate material to obtain uniformly coated powder; and 4) calcining the uniformly coated powder obtained in the step 3) to form the oxide modified positive electrode material. The oxide-modified positive electrode material can be used for remarkably prolonging the cycle life and improving the rate capability of the positive electrode material of the lithium ion battery, and has very high practical value and application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical materials, and specifically relates to an oxide-modified positive electrode material and a preparation method and application thereof. Background Art

[0002] Surface coating, as a very important means of modifying the interface of materials, plays an important role in the fields of batteries, catalysis, gas sensing, etc., especially in the interface protection of battery electrode materials. During the charge and discharge cycle of the battery, the electrode material will undergo an irreversible structural phase change. At the same time, the exposed electrode material interface will have serious interfacial side reactions with the corrosive organic electrolyte, which aggravates the further structural degradation of the material, such as the deepening of cracks caused by electrolyte penetration and the dissolution of transition metal ions, which directly and significantly reduces the cycle stability and safety of the battery. Constructing a protective coating on the surface of the electrode material can significantly alleviate the degradation of the electrode material structure and the occurrence of interfacial side reactions, which has great application value for realizing stable and safe high-energy-density electrode materials.

[0003] Metal oxides have good structural stability and chemical stability, and are often used to stabilize the electrode material interface of the battery. They have good effects in inhibiting the structural phase change of the positive electrode material, crack formation, and the side reaction between the electrode and the electrolyte. Therefore, the structure of the electrode can be significantly stabilized, and the interface impedance of the material can be greatly reduced, thereby greatly improving the cycle performance and rate performance of the battery. In current research, the coating methods of metal oxides mainly include solid phase blending, liquid phase evaporation, atomic layer deposition (ALD) and other methods. Simple solid phase blending and liquid phase evaporation cannot achieve uniform control of the surface of the electrode material, so that the electrode interface cannot be protected to the maximum extent, and it is not conducive to studying the structural relationship of the material. Atomic layer deposition can achieve uniform coating of the material surface, but its high cost, harsh reaction conditions and limited sample processing capacity make it unsuitable for large-scale industrial production. Chinese patent document CN112420997 achieves uniform and controllable coating of oxides on the surface of electrode materials in non-aqueous solvents by using metal salts and slow-release precipitants under gradually heated conditions, but this method is still difficult to achieve uniform coating of large batches of samples. Therefore, there is an urgent need to develop a coating method with mild reaction conditions, low cost, suitable for large-scale industrial scale-up and simultaneous control of the electrode material surface, so as to improve the interface stability of the electrode material. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing an oxide-modified positive electrode material, the preparation method comprising:

[0006] 1) reacting the metal salt with the precursor alcohol solvent for a certain period of time to form a solution A;

[0007] 2) mixing the coated substrate material and the anti-solvent to form solution B;

[0008] 3) mixing the solution A obtained in step 1) with the solution B obtained in step 2) to form a uniform, continuous coating layer with controllable thickness on the surface of the coating substrate material to obtain a uniformly coated powder;

[0009] 4) calcining the uniformly coated powder obtained in step 3) to form the oxide-modified positive electrode material.

[0010] According to an embodiment of the present invention, the precursor alcohol solvent includes but is not limited to one or more of ethylene glycol, propylene glycol, tetraethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600, preferably diethylene glycol.

[0011] According to an embodiment of the present invention, the metal salt is selected from one or more of chlorides of metal elements, sulfates of metal elements, nitrates of metal elements, acetates of metal elements and alkoxides of metal elements. Preferably, the metal element is selected from at least one of niobium, tantalum, hafnium, titanium, aluminum, magnesium, silicon, zirconium, zinc, molybdenum, tungsten, lanthanum, cerium, manganese, iron, nickel, cobalt, copper, yttrium, scandium, holmium, indium and gallium, preferably at least one of niobium, tantalum, titanium, aluminum, magnesium, zirconium, nickel, cobalt, manganese and hafnium.

[0012] According to an embodiment of the present invention, in the solution A, the concentration of the metal salt is 0.001-1 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L.

[0013] According to an embodiment of the present invention, in step 1), the conditions for forming solution A include: the reaction temperature is room temperature to 60°C, preferably room temperature; the reaction time is 2h-72h, preferably 6h.

[0014] According to an embodiment of the present invention, the coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles.

[0015] According to an embodiment of the present invention, the metal material in the coating substrate material includes but is not limited to at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof.

[0016] According to an embodiment of the present invention, the non-metallic material in the coating substrate material includes but is not limited to at least one of carbon, silicon, sulfur, phosphorus and selenium.

[0017] According to an embodiment of the present invention, the oxides in the coated substrate material include but are not limited to at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide.

[0018] According to an embodiment of the present invention, the sulfide in the coated substrate material includes but is not limited to at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide.

[0019] According to an embodiment of the present invention, the carbide in the coating substrate material includes but is not limited to at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide.

[0020] According to an embodiment of the present invention, the nitride in the coating substrate material includes but is not limited to at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride.

[0021] According to an embodiment of the present invention, the phosphide in the coating substrate material includes but is not limited to at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide.

[0022] According to an embodiment of the present invention, the lithium salt positive electrode material in the coated substrate material includes but is not limited to at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate.

[0023] According to an embodiment of the present invention, the sodium salt positive electrode material in the coated substrate material includes but is not limited to at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials.

[0024] According to an embodiment of the present invention, the potassium salt positive electrode material in the coated substrate material includes but is not limited to at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials.

[0025] According to an embodiment of the present invention, the organic particles in the coating substrate material are selected from at least one of phenolic resin particles, urea-formaldehyde resin particles, melamine resin particles, polystyrene particles, polydopamine particles, and polyvinyl pyrrolidone particles.

[0026] According to an embodiment of the present invention, in step 2), the coated substrate material and the anti-solvent are uniformly mixed by ultrasound and high-speed stirring to obtain solution B.

[0027] According to an embodiment of the present invention, in solution B, the concentration of the coating substrate material is 0.01 to 1000 g / L, for example, 0.1 g / L, 1 g / L, 10 g / L, or 100 g / L.

[0028] According to an embodiment of the present invention, the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, acetone, butanone, chloroform, dichloromethane, furfural, acetonitrile, dioxane, ethyl acetate, acetic acid, formic acid, acetic anhydride, acetylacetone, acetaldehyde, and tetrahydrofuran, preferably at least one of acetone, acetonitrile, tetrahydrofuran, and ethyl acetate.

[0029] According to an embodiment of the present invention, in step 3), the method of mixing solution A with solution B comprises: adding solution A to solution B, or adding solution B to solution A. Preferably, the adding refers to: adding by at least one of pouring, slowly dripping, or dripping by controlling the dripping speed through a peristaltic pump.

[0030] According to an embodiment of the present invention, in step 3), the mixing is performed under stirring. Further, the stirring speed of the solution A and the solution B when mixed is between 100 r / min and 1000 r / min, preferably 600 r / min.

[0031] According to an embodiment of the present invention, in step 3), the temperature at which solution A and solution B are mixed is from room temperature to 50° C., preferably room temperature.

[0032] According to an embodiment of the present invention, in step 4), the calcination atmosphere is at least one of oxygen, air, nitrogen and argon.

[0033] According to an embodiment of the present invention, in step 4), the calcination temperature is 200 to 900° C., and the calcination time is 1 to 10 hours.

[0034] The present invention also provides an oxide-modified positive electrode material, wherein the oxide-modified positive electrode material is prepared by the above-mentioned method for preparing the oxide-modified positive electrode material.

[0035] According to an embodiment of the present invention, the oxide-modified positive electrode material is a particle having a core-shell structure.

[0036] According to an embodiment of the present invention, the oxide-modified positive electrode material includes a nano-coating shell layer and a coating substrate material, wherein the nano-coating shell layer is modified on the surface of the coating substrate material; the coating substrate material has the meaning as described above; and the nano-coating shell layer includes an oxide.

[0037] Preferably, the nano-coating shell layer partially or completely coats the surface of the coating substrate material, preferably completely coats the surface of the coating substrate material. Further, the nano-coating shell layer is continuously and evenly distributed on the surface of the coating substrate.

[0038] According to an embodiment of the present invention, the nano-coating shell layer includes oxides of metal elements, such as but not limited to niobium oxide, tantalum oxide, hafnium oxide, titanium oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, molybdenum oxide, tungsten oxide, lanthanum oxide, cerium oxide, manganese oxide, iron oxide, nickel oxide, cobalt oxide, copper oxide, yttrium oxide, scandium oxide, holmium oxide, indium oxide, and gallium oxide, preferably at least one of niobium oxide, tantalum oxide, titanium oxide, aluminum oxide, magnesium oxide, zirconium oxide, hafnium oxide, manganese oxide, nickel oxide, and cobalt oxide.

[0039] According to an embodiment of the present invention, the thickness of the nano-coating shell layer is 0 nm to 500 nm, for example, 1 nm, 1.5 nm, 5 nm, 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, or 400 nm.

[0040] The present invention also provides the use of the above oxide-modified positive electrode material in energy storage batteries.

[0041] Specifically, it is used to construct a high specific energy storage battery; more specifically, it is used to stably construct a high specific energy storage battery.

[0042] Beneficial effects:

[0043] The present invention provides a method for preparing an oxide-modified positive electrode material, which has many advantages, such as mild reaction conditions, simple operation, strong universality, and is suitable for accurately controlling the thickness of the substrate surface coating layer for processing large quantities of samples. This method adopts a simple liquid phase strategy to regulate the surface construction of the coating species and the control of the coating thickness, and utilizes the interaction between metal salts, precursor alcohol solvents, and anti-solvents to achieve a uniform, continuous, and thickness-controlled coating effect on the surface by regulating the feeding rate, etc., and a stable metal oxide coating layer can be obtained after high-temperature treatment. This coating method is suitable for different types of substrates, especially a uniform and controllable nano-coating layer can be obtained on the surface of the electrode material, which significantly improves the cycle stability and rate performance of the battery.

[0044] The method of the present invention can be used to achieve nanoscale coating on the interface of the electrode material of lithium ion batteries or lithium batteries to obtain oxide-coated particles with a core-shell structure. More specifically, it can be used to in-situ construct nanoscale coating materials for the positive electrode materials of lithium ion batteries or lithium batteries.

[0045] The positive electrode material particles with a core-shell structure obtained by the present invention can be used to construct a stable high-energy storage battery.

[0046] The oxide coating method constructed by the present invention utilizes the interaction between metal salt, precursor alcohol solvent and anti-solvent to realize a uniform nano-coating layer on the surface of the coated substrate material, changes the type of anti-solvent, the feeding method between the anti-solvent and the precursor solution and the dripping speed to realize the regulation of the supersaturation of the coated species, and slowly controls the speed of its nucleation and growth to satisfy the growth mode of heterogeneous nucleation, thereby growing a continuous nano-coating layer with uniform thickness on different substrate surfaces. The thickness of the coated shell layer can be effectively regulated by simply controlling the concentration of the metal salt, the content of the substrate and the dripping speed. The coating method has a simple operation process, mild conditions and strong universality, and the formed core-shell structure material has a good application prospect in the energy field.

[0047] The present invention realizes the construction of a uniform oxide nano-coating layer on the surface of the positive electrode material of the lithium ion battery through a simple liquid phase method. This strategy not only stabilizes the interface structure of the positive electrode material, but also significantly blocks the harmful side reactions between the positive electrode material and the organic electrolyte, reduces the material's interface film impedance and charge transfer impedance, promotes the transmission dynamics of lithium ions, and improves the battery's cycle stability and rate performance. In addition, by regulating the thickness of the surface-stable oxide nano-coating layer, it is beneficial to optimize the electrochemical properties of the material, and it is possible to develop a lithium ion battery positive electrode material with both high specific capacity and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a transmission electron microscope photograph of the niobium oxide-coated silicon dioxide nanoparticles of Example 1.

[0049] Figure 2 This is a transmission electron microscope photograph of the niobium oxide-coated single-crystalline silicon nanoparticles of Example 2.

[0050] Figure 3 This is a transmission electron microscope photograph of the niobium oxide-coated micron mica particles of Example 3.

[0051] Figure 4 This is a transmission electron microscope photograph of the niobium oxide-coated micron carbon nanotubes of Example 4.

[0052] Figure 5This is a transmission electron microscope photograph of the niobium oxide-coated spinel lithium nickel manganese oxide of Example 5.

[0053] Figure 6 This is a transmission electron microscope photograph of the 40nm niobium oxide-coated nickel cobalt manganese oxide high-nickel positive electrode of Example 6.

[0054] Figure 7 This is a transmission electron microscope photograph of the 12nm niobium oxide-coated nickel cobalt manganese oxide high-nickel positive electrode of Example 7.

[0055] Figure 8 This is a transmission electron microscope photograph of the 5nm niobium oxide-coated nickel cobalt manganese oxide high-nickel positive electrode of Example 8.

[0056] Fig. 9 This is a transmission electron microscope photograph of the partially coated nickel cobalt manganese oxide high-nickel positive electrode in Comparative Example 2.

[0057] Fig.10 The cycle performance of the corresponding lithium nickel cobalt manganese oxide high-nickel positive electrode particles in Example 8 and Comparative Example 1 and Comparative Example 2 at a charge and discharge current of 200 mA / g. DETAILED DESCRIPTION

[0058] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0059] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0060] The following examples further illustrate the present invention using niobium oxide as an example, and other surface oxide modification methods are basically the same as the following examples. According to the specific reaction system, the corresponding metal salt, precursor solvent, anti-solvent, and coating substrate material are selected, and the reaction of the precursor solution and the anti-solvent is controlled by an appropriate feeding method to achieve a uniform and continuous coating effect, and the thickness of the nano-coating layer is controlled by changing the metal salt concentration, the amount of the coating substrate material, the dripping speed, etc.

[0061] Example 1

[0062] Preparation of NbO2-modified Silica Nanoparticles with Core-Shell Structure:

[0063] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0064] 2) dispersing 0.2 g of silica spherical nanoparticles (500 nm) into 40 ml of acetone, and uniformly dispersing by ultrasonic stirring to form solution B;

[0065] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0066] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form silicon dioxide nanoparticles modified with niobium oxide.

[0067] The niobium oxide modified silica nanoparticles are a typical core-shell structure, as shown in the transmission electron microscopy picture. Figure 1 The core material is nano-silicon dioxide with an average size of about 500nm, the shell thickness is 50nm, and niobium oxide is continuously and evenly distributed on the surface of the silicon dioxide substrate.

[0068] Example 2

[0069] Preparation of single-crystalline silicon nanoparticles modified with niobium oxide having a core-shell structure:

[0070] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0071] 2) Disperse 0.2 g of single crystal silicon nanoparticles (50 nm) into 40 ml of acetone and disperse them evenly by ultrasonic stirring to form solution B;

[0072] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0073] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form single crystal silicon nanoparticles modified with niobium oxide.

[0074] The single crystal silicon nanoparticles modified with niobium oxide have a typical core-shell structure, as shown in the transmission electron microscope photo. Figure 2 The core material is nano-single-crystal silicon with an average size of about 50nm, the shell thickness is 12nm, and niobium oxide is continuously and evenly distributed on the surface of the nano-single-crystal silicon substrate.

[0075] Example 3

[0076] Preparation of micron-sized mica particles modified with niobium oxide having a core-shell structure:

[0077] 1) 0.0.05 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0078] 2) Disperse 0.3 g of micron-sized mica particles (40-60 μm) into 40 ml of acetone and disperse them evenly under ultrasonic stirring to form solution B;

[0079] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0080] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form micron-sized mica particles modified with niobium oxide.

[0081] The micron-sized mica particles modified with niobium oxide are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 3 The core material is composed of mica particles with an average size of about 40-60 μm, the shell thickness is 10 nm, and niobium oxide is continuously and evenly distributed on the surface of the micron-sized mica particle substrate.

[0082] Example 4

[0083] Preparation of niobium oxide-modified micron-sized carbon nanotubes with core-shell structure:

[0084] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0085] 2) Dispersing 0.2 g of micron-sized carbon nanotubes (15-20 μm) into 40 ml of acetone, and uniformly dispersing by ultrasonic stirring to form solution B;

[0086] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0087] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form micron-sized carbon nanotubes modified with niobium oxide.

[0088] The micron-sized carbon nanotubes modified with niobium oxide are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 4 The core material has an average size of about 15-20 μm carbon nanotubes, the shell thickness is 15 nm, and niobium oxide is continuously and evenly distributed on the surface of the micron-sized carbon nanotube substrate.

[0089] Example 5

[0090] Preparation of niobium oxide modified lithium nickel manganese oxide particles with core-shell structure:

[0091] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0092] 2) Disperse 4 g of lithium nickel manganese oxide particles (particle size of 200-500 nm) in 40 ml of acetone, and disperse them evenly by ultrasonic stirring to form solution B;

[0093] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0094] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form lithium nickel manganese oxide particles modified with niobium oxide.

[0095] The niobium oxide modified lithium nickel manganese oxide particles are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 5 The core material is made of lithium nickel manganese oxide particles with an average size of about 200 to 500 nm, the shell thickness is 10 nm, and niobium oxide is continuously and evenly distributed on the surface of the lithium nickel manganese oxide particle base.

[0096] Example 6

[0097] Preparation of niobium oxide modified lithium nickel cobalt manganese oxide high nickel cathode particles with core-shell structure:

[0098] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0099] 2) Disperse 1.0 g of lithium nickel cobalt manganese oxide high nickel positive electrode particles (particle size 1-10 μm) into 40 ml of acetone, and disperse evenly by ultrasonic stirring to form solution B;

[0100] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0101] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form lithium nickel cobalt manganese oxide high-nickel positive electrode particles modified with niobium oxide.

[0102] The high-nickel cathode particles of nickel cobalt manganese oxide modified by niobium oxide are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 6The core material has an average size of about 1-10 μm of lithium nickel cobalt manganese oxide high nickel positive electrode particles, a shell thickness of 40 nm, and niobium oxide is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide high nickel positive electrode particle base.

[0103] Example 7

[0104] Preparation of lithium nickel cobalt manganese oxide high nickel cathode particles with a 12nm niobium oxide coating layer:

[0105] 1) 0.3 ml of niobium ethoxide and 10 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0106] 2) Disperse 4.1 g of lithium nickel cobalt manganese oxide high nickel positive electrode particles (particle size 1-10 μm) into 40 ml of acetone, and disperse them evenly by ultrasonic stirring to form solution B;

[0107] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0108] 4) The uniformly coated powder obtained in step 3) is calcined at 500° C. in an air atmosphere for 2 h to form lithium nickel cobalt manganese oxide high-nickel positive electrode particles modified with niobium oxide.

[0109] The high-nickel cathode particles of nickel cobalt manganese oxide modified by niobium oxide are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 7 The core material has an average size of about 1-10 μm of lithium nickel cobalt manganese oxide high nickel positive electrode particles, a shell thickness of 12 nm, and niobium oxide is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide high nickel positive electrode particle base.

[0110] Example 8

[0111] Preparation of large quantities of lithium nickel cobalt manganese oxide high nickel cathode material particles with a 5nm niobium oxide coating layer:

[0112] 1) 5 ml of niobium ethoxide and 100 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0113] 2) Dispersing 200 g of lithium nickel cobalt manganese oxide high nickel positive electrode particles (particle size of 1-10 μm) into 400 ml of acetone, and uniformly dispersing by ultrasonic stirring to form solution B;

[0114] 3) Solution A was slowly added dropwise to solution B by a peristaltic pump, and stirring was continued at room temperature for 1 hour. After centrifugation, washing, and drying, a uniformly coated powder was obtained;

[0115] 4) The uniformly coated powder obtained in step 3) is calcined at 700° C. in an air atmosphere for 2 h to form lithium nickel cobalt manganese oxide high-nickel positive electrode particles modified with niobium oxide.

[0116] The high-nickel cathode particles of nickel cobalt manganese oxide modified by niobium oxide are typical core-shell structures, as shown in the transmission electron microscope photo. Figure 8 The core material has an average size of about 1-10 μm of lithium nickel cobalt manganese oxide high nickel positive electrode particles, a shell thickness of 5 nm, and niobium oxide is continuously and evenly distributed on the surface of the lithium nickel cobalt manganese oxide high nickel positive electrode material particle base.

[0117] Application Examples

[0118] 1. Preparation of Niobium Oxide Modified Lithium Nickel Cobalt Manganese Oxide High Nickel Electrode

[0119] 0.24 g of the modified positive electrode material particles in the above Example 8 were mixed with 0.03 g of acetylene black, a conductive additive, 0.6 g of PVDF with a binder concentration of 5% by mass, and a small amount of solvent NMP. After slurrying, coating (aluminum sheet as current collector), and drying, niobium oxide-coated lithium nickel cobalt manganese oxide electrode sheets were obtained.

[0120] 2. Assemble the battery

[0121] The prepared niobium oxide-modified lithium nickel cobalt manganese oxide electrode sheet was used as the positive electrode, lithium metal was used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as the separator, and 1.15 mol / L LiPF6 was used as the electrolyte to assemble a button cell in an argon-protected glove box.

[0122] 3. Battery Test

[0123] The above battery was subjected to constant current charge and discharge test using a charge and discharge instrument, with the test voltage range of 2.8 to 4.3 V and the test temperature of 25° C. The battery specific capacity and charge and discharge current were calculated based on the mass of lithium nickel cobalt manganese oxide.

[0124] Comparative Example 1

[0125] 1. Prepare a high-nickel lithium nickel cobalt manganese oxide electrode using uncoated lithium nickel cobalt manganese oxide high-nickel positive electrode material. For specific steps, refer to step 1 of the application example.

[0126] 2. Assemble the battery. For specific steps, refer to step 2 of the application example.

[0127] 3. Battery test. For specific steps, please refer to step 3 of the application example.

[0128] Comparative Example 2

[0129] 1. The preparation of partially coated lithium nickel cobalt manganese oxide positive electrode material is as follows:

[0130] 1) 5 ml of niobium ethoxide and 200 ml of diethylene glycol were stirred at 600 r / min and room temperature for 6 h to form a precursor solution A;

[0131] 2) dispersing 200 g of lithium nickel cobalt manganese oxide high nickel positive electrode particles (particle size of 1-10 μm) into the above-mentioned precursor solution A to obtain a turbid solution, and then centrifuging, washing, and drying to obtain a partially coated powder;

[0132] 3) The powder obtained in step 2) is calcined at 700° C. in an oxygen atmosphere for 2 h to obtain a partially coated positive electrode material.

[0133] 2. Prepare an electrode from the partially coated lithium nickel cobalt manganese oxide prepared in step 1 above. For specific steps, refer to step 1 of the application example.

[0134] 3. Assemble the battery. For specific steps, refer to step 2 of the application example.

[0135] 4. Battery test. For specific steps, please refer to step 3 of the application example.

[0136] Fig. 9 This is a transmission electron microscope image of the partially coated nickel cobalt manganese oxide positive electrode material in Comparative Example 2. The coated species is partially adsorbed on the surface of the positive electrode material, which is in sharp contrast to the uniformly coated nickel cobalt manganese oxide positive electrode material in Example 8.

[0137] Fig.10 The cycle performance of the button cells assembled using the high-nickel positive electrode materials corresponding to Example 8 and Comparative Examples 1 and 2 at a charge and discharge current of 200 mA / g is shown. After 100 cycles, the capacity of the uniformly coated sample in Example 8 is 170 mAh / g (capacity retention rate 94%), which is much higher than 154 mAh / g (capacity retention rate 87%) of the uncoated nickel cobalt manganese oxide after 100 cycles in Comparative Example 1 and 162 mAh / g (capacity retention rate 90%) of the partially coated sample in Comparative Example 2. It can be seen that the surface oxide-modified positive electrode material obtained by the method of the present invention significantly improves the capacity retention rate and life of the coated substrate, and can prepare a positive electrode material with high capacity and high stability.

[0138] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an oxide-modified positive electrode material, characterized in that: The preparation method comprises: 1) reacting the metal salt with the precursor alcohol solvent for a certain period of time to form a solution A; 2) mixing the coated substrate material and the anti-solvent to form solution B; 3) mixing the solution A obtained in step 1) with the solution B obtained in step 2) to form a uniform, continuous coating layer with controllable thickness on the surface of the coating substrate material to obtain a uniformly coated powder; 4) calcining the uniformly coated powder obtained in step 3) to form the oxide-modified positive electrode material.

2. The preparation method according to claim 1, characterized in that: The precursor alcohol solvent includes, but is not limited to, one or more of ethylene glycol, propylene glycol, tetraethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600. Preferably, the metal salt is selected from one or more of chlorides of metal elements, sulfates of metal elements, nitrates of metal elements, acetates of metal elements and alkoxides of metal elements. Preferably, the metal element is selected from at least one of niobium, tantalum, hafnium, titanium, aluminum, magnesium, silicon, zirconium, zinc, molybdenum, tungsten, lanthanum, cerium, manganese, iron, nickel, cobalt, copper, yttrium, scandium, holmium, indium and gallium. Preferably, in the solution A, the concentration of the metal salt is 0.001 to 1 mol / L. Preferably, in step 1), the conditions for forming solution A include: the reaction temperature is room temperature to 60° C.; and the reaction time is 2 h to 72 h.

3. The preparation method according to claim 1 or 2, characterized in that: The coating substrate material is selected from at least one of metal materials, non-metal materials, oxides, sulfides, carbides, nitrides, phosphides, lithium salt positive electrode materials, sodium salt positive electrode materials, potassium salt positive electrode materials, and organic particles.

4. The preparation method according to claim 3, characterized in that: The metal material in the coating substrate material is selected from at least one of gold, silver, ruthenium, rhodium, palladium, platinum, germanium, tin, antimony and alloys thereof. Preferably, the non-metallic material in the coating substrate material is selected from at least one of carbon, silicon, sulfur, phosphorus and selenium. Preferably, the oxide in the coating substrate material is selected from at least one of silicon dioxide, titanium dioxide, aluminum oxide, zinc oxide, magnesium oxide, calcium oxide, manganese dioxide, manganese tetraoxide, iron oxide, iron oxide, cobalt oxide, nickel oxide, vanadium pentoxide, zirconium oxide, molybdenum oxide, indium tin oxide, tin oxide, and lithium lanthanum zirconium oxide. Preferably, the sulfide in the coating substrate material is selected from at least one of zinc sulfide, tungsten sulfide, bismuth sulfide, titanium disulfide, iron sulfide, cobalt sulfide, nickel sulfide, molybdenum sulfide, tin sulfide and antimony sulfide. Preferably, the carbide in the coating substrate material is selected from at least one of silicon carbide, titanium carbide, calcium carbide, vanadium carbide, chromium carbide, tantalum carbide, tungsten carbide and boron carbide. Preferably, the nitride in the coating substrate material is selected from at least one of boron nitride, gallium nitride, silicon nitride, titanium nitride, vanadium nitride, niobium nitride, tungsten nitride and phosphorus nitride. Preferably, the phosphide in the coating substrate material is selected from at least one of iron phosphide, cobalt phosphide, nickel phosphide, titanium phosphide, molybdenum phosphide and tin phosphide. Preferably, the lithium salt positive electrode material in the coating substrate material is selected from at least one of lithium titanate, lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium-rich nickel cobalt manganese oxide, lithium titanium phosphate, lithium titanium aluminum phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and lithium manganese cobalt phosphate. Preferably, the sodium salt positive electrode material in the coating substrate material is selected from at least one of oxide sodium salt positive electrode materials, polyanion sodium salt positive electrode materials, Prussian blue sodium salt positive electrode materials, fluoride sodium salt positive electrode materials, and organic compound sodium salt positive electrode materials. Preferably, the potassium salt positive electrode material in the coating substrate material is selected from at least one of Prussian blue-based potassium salt positive electrode materials, layered oxide-based potassium salt positive electrode materials, polyanion-based potassium salt positive electrode materials, and organic material-based potassium salt positive electrode materials. Preferably, the organic particles in the coating substrate material are selected from at least one of phenolic resin particles, urea-formaldehyde resin particles, melamine resin particles, polystyrene particles, polydopamine particles, and polyvinyl pyrrolidone particles.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In solution B, the concentration of the coating substrate material is 0.01 to 1000 g / L. Preferably, the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, acetone, butanone, chloroform, dichloromethane, furfural, acetonitrile, dioxane, ethyl acetate, acetic acid, formic acid, acetic anhydride, acetylacetone, acetaldehyde, and tetrahydrofuran.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step 3), the method of mixing solution A and solution B includes: adding solution A to solution B, or adding solution B to solution A. Preferably, the adding refers to adding by at least one of pouring, slowly dripping or dripping by controlling the dripping speed through a peristaltic pump. Preferably, the mixing of solution A and solution B is carried out under stirring; preferably, the stirring temperature is room temperature to 50° C.; further preferably, the stirring speed is between 100 r / min and 1000 r / min.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step 4), the calcination atmosphere is at least one of oxygen, air, nitrogen and argon. Preferably, in step 4), the calcination temperature is 200 to 900° C., and the calcination time is 1 to 10 hours.

8. An oxide-modified positive electrode material, characterized in that: The oxide-modified positive electrode material is prepared by the preparation method according to any one of claims 1 to 7.

9. The positive electrode material according to claim 8, characterized in that The oxide-modified positive electrode material is a particle with a core-shell structure. Preferably, the oxide-modified positive electrode material comprises a nano-coating shell layer and a coating substrate material; the coating shell layer comprises an oxide. Preferably, the nano-coating shell layer partially or completely coats the surface of the coating substrate material. Preferably, the nano-coating shell layer is an oxide of a metal element. Preferably, the thickness of the nano-coating shell layer is 0 nm to 500 nm.

10. Use of the oxide-modified positive electrode material according to claim 8 or 9 in energy storage batteries.

Citation Information

Patent Citations

  • Preparation method of WO3 modified nickel-rich ternary lithium ion battery positive electrode material

    CN111916730A

  • Silicon-based negative electrode material, preparation method thereof and application of silicon-based negative electrode material in lithium ion battery

    CN113594455A

  • Alumina-coated NCM positive electrode material and preparation method and application thereof

    CN115504523A

Cited By

  • Preparation method of Mn3O4 / CoP2 / NF three-dimensional heterostructure electrode material for sodium ion battery and sodium ion battery

    CN121601638A

  • High-strength hard alloy material and preparation method thereof

    CN122168959A